Persistensi laba dalam perspektif keagenan - Rumawas, Alda Gabriela; Pontoh, Winston; Korompis, Claudia W. M. (Riset Akuntansi dan Manajemen Pragmatis, 2025)
This study aims to empirically examine the effect of operating cash flow volatility, debt to asset ratio (DAR), and the size of accruals on earnings persistence in healthcare sector companies listed on the Indonesia Stock Exchange. This is a quantitative study using secondary data. The sampling technique used is purposive sampling, resulting in a sample of 11 companies over a research period of 5 years, producing a total of 55 research data points. The data analysis technique used is multiple linear regression with Jamovi software. The partial results of the study show that operating cash flow volatility and the size of accruals have a significant effect on earnings persistence, while the debt to asset ratio (DAR) does not have a significant effect on earnings persistence. Simultaneously, operating cash flow volatility, debt to asset ratio, and the size of accruals together have a significant effect on earnings persistence.